Réponses

2014-05-18T18:31:43+02:00
Salut :) 

a) (x+7)²=9
(x+7)(x+7)=9
x × x + x × 7 + 7 × x + 7 × 7 = 9 
x² + 14x + 49 = 9
x= - 10   ou  x = - 4

b) (x-5)²=16
(x-5)(x-5)=16
x²-10 x+25 = 16

x= 1  ou  x= 9
2014-05-18T19:49:55+02:00
a) (x+7)²=9
    (x +7)² - 9 = 0
    (x +7)² - 9 = 
(x +7)² - 3²
    (x +7 -3)(x +7 +3) = (x - 4)(x+10)
    (x - 4)(x+10) = 0
    (x - 4) = 0                             ou               (x+10) = 0
     x -4+4 = 0+4                                           x +10-10= 0-10
            x = 4                                                         x =  -10

        b) (x-5)²=16
             (x -5)² -16 =0
            (x -5)² -16 = (x -5 )² - 4²
             (x-5+4)(x-5-4) = (x -1)(x -9
              (
x -1)(x -1)(x -9) = 0 
                
               (x -1) =0                                   ou                          (x -1) = 0
                x -1 +1= 0+1                                                          x-1+1 = 0 +1
                        x = 1                                                                   x = 1